Criopreservação do sêmen de búfalos (Bubalus bubalis) em diluidores contendo lipoproteínas de baixa densidade, em substituição a gema de ovo - Mayara Ferreira Brito (2014)
The aim of this study was analyze the effect of different extenders, consisting of egg yolk chicken or low density lipoproteins extracted from egg yolk, during the process of sperm cryopreservation of buffalo bulls in order to define which provides greater protective effect on sperm characteristics. This work was divided into three phases: Pre - experiment , Experiment 1 and Experiment 2 . The purpose of the Pre-experiment was to compare three extenders, including a commercial, that have the egg yolk as a common component. In Experiments 1 and 2 compared different concentrations of LDL in semen extenders chosen at pre - experiment. Ejaculates from six Murrah buffaloes were divided and diluted according to the stage: Pre- experiment - Diluidor comercial, Tes- Tris , Tris- citric acid; Experiment 1 Full commercial extender , commercial extender + 2 % LDL, commercial extender + 4%LDL, commercial extender + 8 % LDL, commercial extender + 14 % LDL; Experiment 2 - Tes- Tris , Tes- Tris + 2 % LDL, Tes- Tris + 4 %LDL , Tes- Tris + 8%LDL , Tes- Tris + 14% LDL . The samples of experiments 1 and 2 were analyzed by CASA in pre-cooling . At all stages thawed samples were submitted to the thermotolerance test , assisted by CASA , hypoosmotic test and integrity of membranes by fluorescent probes ( CFDA / Pi ). The average results of these three tests were compared by Tukey test (P < 0.05 ) . In Pre - experiment post -thaw motility were similar, 40.97 ± 14.21 , 37.13 ± 10.12 , 32.81 ± 11.78 respectively for commercial extender, Tes- Tris , Tris - citric acid. From reading the 30 minutes commercial extender and Tes- Tris extenders showed superiority for motility, compared to Tris - citric acid. The values of VCL , VSL , VAP , LIN and BCF were higher for full commercial extender, and similar to Tes-Tris and Tris -citric acid. There was no difference between treatments regarding the integrity of membranes. In Experiment 1 the full commercial extender was superior to the motility, VCL , VSL , VAP , LIN and BCF in pre dilution, post-thawing periods and throughout the TTR . The 2%LDL concentration had lower effect to preserve the integrity of the membranes to full commercial extender. In Experiment 2 the Tes- Tris was less than 2 and 4% LDL for motility in pre-cooling. In the post - thaw motility the Tes- Tris was higher (56.53 ± 9.73 ) to all LDL concentrations ( 47.16 ± 11.06 , 45.64 ± 7.46 , 45.71 ± 6 , 56; 43.33 ± 5.97 for 2 , 4, 8 and 14% LDL) . However, during the TTR motilities were similar between all extenders. The Tes- Tris was lower at all concentrations of LDL for VCL , VSL , VAP , LIN and BCF at pre -cooling, post-thaw and throughout the TTR . There was no difference between treatments regarding the integrity of membranes. The extender full commercial extender was more suitable for the freezing of buffalo semen. The concentrations of 2, 4 and 8% of LDL, in basic medium Tes- Tris, were more effective than Tes- Tris extender containing 20% of egg yolk for freezing sperm buffalo.